Perbandingan Titer IgA-EBV pada Orang Sehat di Populasi Umum dan Keluarga Penderita Kanker Nasofarings - , GABRIELLA ARGY; , dr. Susanna Hilda H., SpPD, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Nasopharyngeal cancer (NPC) is the most common head and neck malignancy found in Indonesia. Epstein-Barr Virus is associated with NPC. Screening method have been developed by detecting antibody against EBV in high risk groups such as healthy people with high level of IgA-EBV titer and first degree family of NPC patients. Objectives: To compare the distribution of IgA-EBV titer in non-family healthy individuals and first degree family of NPC patients. Method: Blood samples and demographic data were taken from PMI healthy blood donors. Serum was analyzed using indirect ELISA method to determine IgA EBV titer. Distribution of IgA EBV titer was analyzed according to sex, age, education level and was compared to first degree family of NPC patients (secondary data). Result: Seventy nine point nine percent of healthy nonfamily individuals and 58,3% of first degree families had IgA EBV titer below 0,350. There was significant difference in the distribution of IgA EBV titer between healthy nonfamily individuals and first degree families (p<0,001). The distribution of IgA EBV titer in healthy non-family individuals was different significantly between male and female (p=0,008). However, in first degree families, the distribution of IgA EBV level was not significantly different among sexes (p=0,693), groups of age (p=0,298), and education levels (p=0,409). Furthermore, the correlation between family history of NPC and the distribution of IgA EBV titer was observed in male (p<0,001), less than 40 years old individuals (p<0,001), and individuals who have lower education level than high school (p<0,001). Conclusion: The distribution of IgA EBV titer was different between healthy non-family individuals and first degree families of NPC patients. The difference was observed in male, less than 40 years old individuals, and individuals who have lower education level than high school.